PENGARUH PERHATIAN ORANG TUA DAN FASILITAS BELAJAR DI RUMAH TERHADAP PRESTASI BELAJAR KELISTRIKAN OTOMOTIF SISWA KELAS XI SMK MUHAMMADIYAH IMOGIRI TAHUN PELAJARAN 2012 / 2013 - Nuryanto Nuryanto (Jurnal Taman Vokasi, 2013)
This research intent to know: oldster attention influence and studying facility on the house to belistrikan otomotif's learned achievement student brazes XI SMK Muhammadiyah Imogiri.This research is observational expost facto and this research is executed di SMK Muhammadiyah Imogiri brazes XI school year 2012 / 2013 by populations that total 204, meanwhile its sample total 126 student that point Harry King's nomogram, sample take in observational it utilizes random is sampling . Data collecting tech utilizes to methodic questionnaire, Validity numbers problem got by correlation product moment ,. analisis's tech data that is utilized is analisis descriptive, analisis's stipubting quiz (normality quiz, linieritas and multikolinieritas), partial correlation and analisis is double regression two Â prediktor.This observational result points out that: Attentions Relative contribution Oldster as big as 55,14%, Facilities Relative contribution Study On The House as big as 44,86%, Attentions Effective contribution Oldster as big as 20,50%, Facilities Effective contribution Study On The House as big as 16,68%.